Arkitekten Hans Westman, funktionalismen och den regionala särarten - Tägil, Tomas (Arkitekturmuseets Skriftserie, 1996)
This thesis deals with the regional aspects of Swedish modernism exemplified by the architecture of Hans Westman (1905-1991). The main purpose of the dissertation has been to make a survey of what is perceived as particularly regional in Westman's buildings and if we can really talk about modern regional architecture. Modernism's breakthrough brought about the introduction of an architecture which was meant to be international in style. Gradually however, both individual and regional differences emerged in architectural practice. This development raised a great interest among architects such as Kenneth Frampton, who in his work "Critical Regionalism" examines the connection between modern and regional architecture. Skåne, Sweden's most Southern province, can be considered a region with its own distinct building tradition. Despite a flood of impulses from outside, rather than being wiped out, the regional peculiarities have instead been fused with modern architecture. Hans Westman, who practised as an architect in Skåne from 1932 until 1983, used this consciously in his architecture. He attempted to unite functionalism with the building traditions of Skåne. In doing so, rather than continuing a "true" tradition, he attempted to create a new distinctive regional architecture which was in reality more "Westmanian" in its expression. Westman began as an out-and-out functionalist and throughout the rest of his life he continued to profess his belief in modern architecture. However, he made one reservation against the functionalists, who didn't take account of the so-called "human factor". In this rather unclear term, Westman reveals his critical position towards functionalist architecture and also its deficiencies: the large scale, the monotonous repetition, the engineering style and the routine approach. It was out of this critical attitude that the motive for a more human modern architecture developed. Westman saw regional references as an essential part of this aspiration.
Keywords: Arkitektur; inredningsarkitektur; interior design; Architecture; Regional Characteristics; Critical Regionalism; Hans Westman; Skåne; Swedish Architecture; Building Tradition; Regionalism; Functionalism; Modern Architecture; 20th Century